Lean process design for a radiology department - Camgöz-Akdag, Hatice; Çaliskan, Esra; Toma, Sirel (Emerald, 2017)
Purpose The purpose of this paper is to design a future value stream map of the system and patient pathway with lean health care application tools in terms of quality improvement (QI) in order to decrease the non-value-added activities for patients, doctors, and nurses for a radiology unit in a public hospital based in Istanbul, Turkey. Design/methodology/approach Data are collected from personal observations, information technologies unit, and authorized employees. In order to measure subprocesses, some qualitative data are transformed into quantitative data via authorized employees’ experiences. Moreover, data tracking and keeping systems are too poor for revealing the current situation. Findings The current value stream map of the system of the radiology department of a public education and research hospital was analyzed and the future value stream map of the system and patient pathway was redesigned with lean health care application tools in terms of QI. Research limitations/implications The greatest limitation is the resistant to change and fear of talking on mistakes and low performances. Originality/value This paper states an example of a current and future value stream map showing step by step where the bottlenecks are and how these can be improved and what specific benefits will this analysis bring to the health care system. It will be useful for both academicians and practitioners on how to apply lean to health care.